Застосування безпілотних літальних систем як мобільних комплексів радіозв’язку - Мельников, С.В.; Волков, О.Є.; Коршунов, М.В.; Грищенко, Ю.Ю. (Управляющие системы и машины, 2017)
Розглянуто застосування сучасних безпілотних літальних апаратів як мобільних комплексів радіозв’язку та передачі даних з метою розширення зони покриття інформаційно-комунікаційної мережі з використанням як окремих систем, так і об’єднаних у мережу. Рассмотрено применение современных беспилотных летательных аппаратов в качестве мобильных комплексов радиосвязи и передачи данных с целью расширения зоны покрытия информационно-коммуникационной сети с использованием как отдельных систем, так и объединенных в сеть. Purpose: The purpose of this research is to review the application of the modern unmanned aerial vehicles as the mobile radio communication and data transmission systems in order to expand the information and communication network coverage area by using either single unmanned aerial systems or such unmanned aerial systems, which are networked to each other. Methods: The proposed system is based on retransmitting the signals among unmanned aerial systems and satellites to consumers. Results: The development of the system of increasing cellular coverage using the unmanned aerial systems and the implementation of the algorithms to expand the information and communication network coverage area. Discussion: The system can be implemented as a single unmanned aerial aircraft with retransmission equipment, as well as a set of such unmanned aerial systems, using ground-to-aircraft, aircraft-to-aircraft and satellite data communication. Such systems ensure the communications and are able to reposition itself in real time in manual and automatic modes.